D-erythro-Sphingosine and Pregnenolonesulphate activate TRPM3 channels synergistically in INS- 1E cells (Bangladesh Journal of Medical Science, 2017)
Background: A group of ion channels have recently been studied to understand the pathogenesis of diabetes. The transient receptor potential (TRP) channels are thought to be involved in many cellular functions. TRPM3, a member of the melastatin-like transient receptor is mainly expressed in human kidney and brain. It is also expressed in human pancreas. Therefore, it is desirable to find compounds able to induce an increase of intracellular calcium([Ca2+]i) in pancreatic ? cells thereby trigger insulin secretion.Aims: The aim of the study was to confirm whether D-erythro- Sphingosine and Pregnenolonesulphate activates TRPM3. Another aim was to investigate whether pancreatic ? cells express TRPM3-channels. INS-1E cells were used as a model of ?cells for [Ca2+]i measurement.Results: Application of endogenous neurosteroidpregnenolonesulphate (35 µM) led to a rapid Ca2+ influx in INS-1E cells and pancreatic beta cells. When PS was applied in the absence of extracellular Ca2+ the [Ca2+]i response to PS was completely lost. The increase in [Ca2+]i induced by PS was inhibited by cholesterol.Western blot data identified a protein reacting specifically with polyclonal antibodies for TRPM3.Conlusion: Our results demonstrate that both pancreatic ?cells and INS-1E cells express functional TRPM3-channels and both SPH and PS are TRPM3 agonists.Bangladesh Journal of Medical Science Vol.16(1) 2017 p.98-106